The Securopolis: (Re)assembling Surveillance, Resilience, and Affect - Rogers, Peter; Justus Liebig University Giessen (My University, 2018)
This paper explores how modern urban life is being re-assembled into a securopolis. The securopolis is a form of urban life in which humans enact a watchfulness (i.e. surveillance) combined with a readiness for the worse (i.e. resilience) which is embedded into the physical and affective (emotional) fabric of the urban. The securopolis is more than a neat model of a safe, secure and sustainable city; it is a powerful influence on the underlying habitus of urban space, culture and governance. To explore this phenomenon the interplay of surveillance and resilience with the perceived needs: to be safe, to improve security and to improve sustainability are unpacked. I argue that this reconfiguration of the urban results in a suite of emergent (and ongoing) challenges; shifting the balance underpinning our traditional concepts of democratic community and publicness. These tensions are (re)configured differently to those so well described by recent research into urban gentrification, militarization and the reimagined boundaries of public/private space. In order to get to grips with them a different approach, with a rethinking of affective governance is required.
Keywords: affect; resilience; security; securopolis; surveillance; ddc:300